Design of An IOT-Based Voltage and Current Monitoring System and Turbine Performance Analysis In A Micro Hydro Power Plant - Syahbana, Zaka; Setiadi, Rizki (Universitas Negeri Semarang, 2025)
Microhydro power plants (MHPP) are a potential renewable energy solution for remote areas that have abundant water resources. However, monitoring the performance of MHPP systems in these areas is still a challenge, especially in terms of reliability and energy conversion efficiency. This research aims to design and develop an Internet of Things (IoT)-based monitoring system capable of monitoring real-time voltage and current in MHPs. The system was tested using the Archimedes Screw turbine in a laboratory-based test scale, and a literature study was conducted to compare the effectiveness of several types of micro hydro turbines such as Pelton, Crossflow, Turgo, and Archimedes Screw. The results showed that although the efficiency of screw turbines is relatively lower, they are suitable for use in locations with low head and stable water flow. The 4D approach method was used in the development of this monitoring system, and the results show that the system is able to provide accurate data and support the improvement of MHPP operational reliability.